Developing a Collaborative Approach to Standpoint in Indigenous Australian Research - Simone Ulalka Tur; Faye Rosas Blanch; Christopher Wilson (The Australian Journal of Indigenous Education, 2010)
Abstract The notion of Indigenous epistemologies and “ways of knowing” continues to be undervalued within various academic disciplines, particularly those who continue to draw upon “scientific” approaches that colonise Indigenous peoples today. This paper will examine the politics of contested knowledge from the perspective of three Indigenous researchers who work within Yunggorendi First Nations Centre for Higher Education and Research at Flinders University in South Australia. In particular, the authors outline a collective process that has emerged from conversations regarding their research projects and responding to what Ladson-Billings and Donnor (2008, p. 371) refer to as the “call”. In developing an Indigenous standpoint specific to their own disciplines and their research context, the authors demonstrate how these collective conversations between each other and their communities in which they work have informed their research practices and provided a common framework which underpins their research methodologies.